2019
DOI: 10.1371/journal.pone.0224705
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia inhibits TNF-α-induced TSLP expression in keratinocytes

Abstract: The expression of thymic stromal lymphopoietin (TSLP), a cytokine which greatly contributes to the induction of type I allergy, is upregulated in chronic inflammation such as atopic dermatitis and psoriasis. As hypoxia in the epidermis is important for maintaining skin homeostasis, we examined the regulation of TSLP expression by hypoxic conditions in normal skin epithelial tissues. TNF-α-induced expression of TSLP in human keratinocyte HaCaT and in mouse keratinocyte PAM212 cell lines were inhibited under hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Furthermore, the results showed that the longer the prenatal hypoxia is, the higher the TNF value will be. It aligns with the previous research [19], [20], [21], revealing that hypoxia causes an increase in TNF [22], [23]. TNF-α is produced from various cells such as lymphoid cells, cardiac myocytes, activated macrophages, endothelial cells, mast cells, fibroblasts, neurons, and adipose tissue.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the results showed that the longer the prenatal hypoxia is, the higher the TNF value will be. It aligns with the previous research [19], [20], [21], revealing that hypoxia causes an increase in TNF [22], [23]. TNF-α is produced from various cells such as lymphoid cells, cardiac myocytes, activated macrophages, endothelial cells, mast cells, fibroblasts, neurons, and adipose tissue.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is unusual, considering that, at least some cytokines, appear to be more prominently represented in the acute phase of Pso rather than AD [ 34 ]., AD has been thoroughly studied in relation to both types of dermatoses, but Pso might represent an interesting field of study. In particular, the role of TNF-alpha should be evaluated, since TSLP appears to be conducive to an increase in TNF-alpha activity [ 35 , 37 ] and several molecules have been used so far to treat Pso by targeting TNF-alpha [ 63 ]. It is plausible to suggest that, since TNF-alpha treatments could lead to several side effects, including the development of new Pso lesions [ 64 ], targeting a molecule down the same pathway, in this case TSLP, could lead to better results in terms of skin clearance and less side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Tashiro et al, using cultures of HaCaT cells (immortalized keratinocytes), found that TSLP, in hypoxic conditions, presents reduced levels via the inactivation of its production stimulated by TNF-alpha, via HIF2 and HRE mechanisms (two products involved in the skin response to hypoxemia). It is the authors’ suggestion that targeting these two molecules could lead to lower levels of TSLP and the resolution of lesions both in Pso and AD [ 37 ]. Schaper et al correlated the levels of TSLP from human skin samples derived from healthy controls, Pso patients and AD patients, noticing that both Pso and AD patients, but mostly Pso patients, presented higher levels of TSLP, especially the inflammation-related isoform rather than the basal one, via histamine release by hyper-active Th2 cells [ 34 ].…”
Section: Psoriasis: Role Of Epithelium Derived Cytokines In Skin Damagementioning
confidence: 99%
“…HIF‐1α potentiates macrophage‐mediated immunity against L major and L amazonensis 89,90 . Hypoxia suppresses the expression of TSLP (a TH2 cell enhancer) in keratinocytes 91 . The wound healing is impaired in aged mice losing HIF‐1α in their keratinocytes 87 .…”
Section: Discussionmentioning
confidence: 99%